Leaf micromorphological and anatomical investigation of Cinnamomum mercadoi Vidal (Kalingag) - Pedrosa, Nikka Flor P.; Tan, Irene L. (2014)
Cinnamomum mercadoi Vidal, commonly known as 'Kalingag', is a vulnerable and endemic species in the Philippines. This is the first attempt to characterize the leaf micromorphological and anatomical features of C. mercadoi. This study will also contribute to the existing information about this species. For leaf micromorphological analysis, mature leaf samples were examined by scanning electron microscopy. On the other hand, internal anatomical structures were obtained in mature leaves using free hand sectioning methods. Freehand sectioned samples were stained with Toluidine Blue O stain and were examined bi light microscopy. Scanning electron micrographs revealed a smooth, wavy, and thick cuticle that covers the adaxial surface. Transverse sections showed the different structures found in the leaf. The midrib is composed of parenchyma cells, continuous zone of sclerenchyma, and vascular bundle that is arc-shaped. Also, the mesophyll layer is dorsiventrally oriented with oil cells found in between cells. These newly described anatomical structures will be useful in taxonomic characterization and species identification.
Undergraduate thesis (B.S. in Biology)--University of the Philippines, Tacloban.
Keywords: Cinnamomum mercadoi Vidal -- leaf micromorphological; Cinnamomum mercadoi Vidal -- anatomical investigation; Cinnamomum mercadoi Vidal(Kalingag), Description; Science and Technology